ANALISIS PERKEMBANGAN JUMLAH PEMBIAYAAN MUDHARABAH DAN MURABAHAH SERTA RASIO PROFITABILITAS PADA BANK SYARIAH MANDIRI CABANG MAKASSAR - AM, Sanusi; Jama, Andi; Pandillahi, Pandillahi (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
The purpose of this study is to analyze the effect of profit sharing financing and partial sale financing on profitability level -Return On Asset (ROA) - PT Bank Syariah Mandiri Makassar Branch with the purpose To examine the effect of financing the results and partial sale financing to the level of profitability -Return On Asset (ROA) - PT Bank Syariah Mandiri Makassar Branch. Data collection using documentation while the type of data used is quantitative data sourced from company reports. The data obtained were analyzed using multiple regression statistical analysis. Based on the results of partial significance test data processing (Test-t) obtained that the variables of profit sharing (X1) and buying and selling (X2) have a significant influence on the dependent variable (ROA). Meanwhile, based on hypothesis test result simultaneously (F test) where H0 is rejected which means that independent variables (financing of profit sharing and selling pattern) have a significant influence together to dependent variable (ROA).